2004
DOI: 10.1124/dmd.32.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Inhibition of Human Cyp3a in Vitro by Azamulin and Evidence That Inhibition Is Irreversible

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Azamulin [14-O-(5-(2-amino-1,3,4-triazolyl)thioacetyl)-dihydromutilin] is an azole derivative of the pleuromutilin class of antiinfectives. We tested the inhibition potency of azamulin toward 18 cytochromes P450 using human liver microsomes or microsomes from insect cells expressing single isoforms. In a competitive inhibition model, IC 50 values for CYP3A (0.03-0.24 M) were at least 100-fold lower than all other non-CYP3A enzymes except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
98
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 28 publications
14
98
0
Order By: Relevance
“…Apart from these, there are further contradictory findings. Parker et al [171] emphasized that the hypothesis of involvement of CYP3A4 in the metabolism of vitamin E is only based on the assumption of ketoconazole specificity, which proved incorrect [172] . Testing recombinant human CYP3A4 in insect cell derived microsomes revealed no activity towards α-or γ-TOH [140] , whereas a systematic screening of other CYP enzymes showed tocopherol-ω-hydroxylase activity only for CYP4F2 [171] (for further details, see the section on CYP4F2 in chapter "metabolism of vitamin E").…”
Section: Cyp3a4mentioning
confidence: 99%
“…Apart from these, there are further contradictory findings. Parker et al [171] emphasized that the hypothesis of involvement of CYP3A4 in the metabolism of vitamin E is only based on the assumption of ketoconazole specificity, which proved incorrect [172] . Testing recombinant human CYP3A4 in insect cell derived microsomes revealed no activity towards α-or γ-TOH [140] , whereas a systematic screening of other CYP enzymes showed tocopherol-ω-hydroxylase activity only for CYP4F2 [171] (for further details, see the section on CYP4F2 in chapter "metabolism of vitamin E").…”
Section: Cyp3a4mentioning
confidence: 99%
“…2A), a competitive CYP4A inhibitor. The appreciable inhibition by ketoconazole was not diagnostic for a major role of CYP3A4/5 because this presumed selective CYP3A4/5 inhibitor has been shown to inhibit other P450s at low concentrations, including CYP4F2 (Wang et al, 2006), CYP1A1 (Paine et al, 1999), and CYP2J2 (Stresser et al, 2004). A minor role of CYP3A4/5 is further supported by 1) the minimal inhibitory effects of both the selective mechanism-based CYP3A4/5 M arachidonic acid, and 1 mM NADPH.…”
Section: Discussionmentioning
confidence: 99%
“…Ketoconazole (Wrighton and Ring, 1994;Newton et al, 1995;Ghosal et al, 1996;Desai et al, 1998;Masimirembwa et al, 1999) and azamulin (Stresser et al, 2004) (both CYP3A4-selective inhibitors) were shown to be potent inhibitors of vicriviroc metabolism by human liver microsomes, suggesting the involvement of CYP3A4 in its metabolism. Stresser et al (2004) reported that azamulin is a highly potent and selective inhibitor of CYP3A.…”
Section: Discussionmentioning
confidence: 99%